Mi Basah dengan Substitusi Tepung Tempe Koro Benguk (Mucuna pruriens L.) dan Ekstrak Pektin Albedo Jeruk Bali (Citrus maxima) - Subagio, Aluysia; Pranata, Franciscus S; Swasti, Yuliana R (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
Wet noodles are noodles made from wheat flour and cooked by boiling. However, wet noodle generally lack nutrients, prompting research to address this issue. This study utilizes velvet bean flour as a partial substitute for wheat flour and pectin extracted from pomelo albedo as a binding agent. The aims are to assess the chemical, physical and microbiological qualities of wet noodles formulated with velvet bean flour and pomelo albedo pectin extract, as well as to determine the optimal concentration that yields the best product quality. The researchers aim to utilize velvet beans for their protein-rich nutritional function and to make use of pomelo albedo waste. A completely randomized design was used with 4 treatment levels consisting of ratios of wheat flour, velvet bean flour, and pomelo albedo pectin extract: 100:0:0 (K),70:25:10 (A), 70:20:15 (B), and 70:15:20 (C). The data were analyzed using the one-way ANOVA method with a 95 % confidence level, followed by DMRT to determine the significant differences among treatments. The results indicate that wet noodles had moisture content ranging from 60,31-63,45 %., ash content 0,5-0,71 %, fat content 0,53-1,76 %, protein content 5,06-8,9 %, carbohydrate content 25,44-31,73 %, insoluble fiber 4,53-11,1 %, soluble fiber 13,-21,67 %, cooking loss 4,92-11,8 %, tensile strength 0,003-0,0055, total plate count and yeast mold count meeting the SNI 2987:2015 quality standard. The formulation with the best overall quality was 70:15:20.